Seasonal Subsurface Thaw Dynamics of an Aufeis Feature Inferred From Geophysical Methods. Issue 3 (18th March 2020) - Terry, Neil; Grunewald, Elliot; Briggs, Martin; Gooseff, Michael; Huryn, Alexander D.; Kass, M. Andy; Tape, Ken D.; Hendrickson, Patrick; Lane, John W.
Abstract: Aufeis are sheets of ice unique to cold regions that originate from repeated flooding and freezing events during the winter. They have hydrological importance associated with summer flows and winter insulation, but little is known about the seasonal dynamics of the unfrozen sediment layer beneath them. This layer may support perennial groundwater flow in regions with otherwise continuous permafrost. For this study, ground penetrating radar (GPR) were collected in September 2016 (maximum thaw) and April 2017 (maximum frozen) at the Kuparuk aufeis field on the North Slope of Alaska. Supporting surface nuclear magnetic resonance data were collected during the maximum frozen campaign. These point‐in‐time geophysical data sets were augmented by continuous subsurface temperature data and periodic Structure‐from‐Motion digital elevation models collected seasonally. GPR and difference digital elevation model data showed up to 6 m of ice over the sediment surface. Below the ice, GPR and nuclear magnetic resonance identified regions of permafrost and regions of seasonally frozen sediment (i.e., the active layer) underlain by a substantial lateral talik that reached >13‐m thickness. The seasonally frozen cobble layer above the talik was typically 3‐ to 5‐m thick, with freezing apparently enabled by relatively high thermal diffusivity of the overlying ice and rock cobbles. The large talik suggests that year‐round groundwater flow and coupled heat transport occurs beneath much of the feature. Highly permeable alluvial material and discrete zones of apparent groundwater upwelling indicated by geophysical and ground temperature data allows direct connection between the aufeis and the talik below. Key Points: A multimethod approach revealed a perennial suprapermafrost groundwater flow system below an arctic aufeis field that supports a spatially extensive lateral talik Groundwater upwelling zones through several meters of frozen cobbles maintain direct connection between surface ice and the lateral talik during winter A revised conceptual hydrogeological model is developed for aufeis fields with extensive lateral groundwater flow